Effective Technique Using Combined CO2 Laser and Pulsed Dye Laser for Facial Angiofibromas Management in Tuberous Sclerosis - Giuseppe Lodi; Giovanni Cannarozzo; Irene Fusco; Tiziano Zingoni; Elena Campione; Mario Sannino (Case Reports in Dermatological Medicine)
Background. Facial angiofibromas (FAs) are a dermatological characteristic which are typically linked to tuberous sclerosis (TS). Aim. We discuss our experience, highlighting a rare occurrence of multiple FAs in a young patient, successfully treated with ablative CO2 laser combined with PDL therapy. Methods. A 23-year-old male patient affected by TS who presents multiple erythematous and colored papules/nodules located on the face, mainly concentrated around nose, perinasal area, cheeks, and chin area, was treated with a combination of ablative CO2 laser and a pulsed dye laser. The patient underwent 3 sessions of combined treatment with CO2 and pulsed dye laser. The intralesional dye laser treatment was administered immediately after the CO2 laser session. The time interval between the combined laser treatments was approximately two months. Results. After 4 months from the last laser treatment session, most of the facial erythematous and protruding lesions had improved. Following these procedures, the patient did not experience complications or severe adverse reaction. Conclusion. The combined use of the CO2 and dye laser has been proved to be a safe and effective treatment for multiple FAs in the young patient affected by tuberous sclerosis.